2007
DOI: 10.4040/jkan.2007.37.2.213
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Culture on the Experiences of Korean, Korean American, and Caucasian-American Family Caregivers of Frail Older Adults: A Literature Review

Abstract: As the size of the frail older adult population increases, family caregiving is becoming a more important issue. Caring for frail older relatives has been regarded as both a challenging and rewarding experience. Recently, some published literature reviews have revealed that culture influences the experiences of family caregivers (Aranda & Knight, 1997;Connell & Gibson, 1997;Dilworth-Anderson, Williams, & Gibson, 2002;Janevic & Connell, 2001).Culture is located inside a human's head, not outside (De Munck, 2000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 31 publications
2
27
0
Order By: Relevance
“…Some caregiving experiences of later generations, such as helping with English translation, were similar to what scholars (Kong, 2007; Mokuau & Tomioka, 2010; Sun et al, 2012) previously found among 1st-generation caregivers. Second-generation caregivers with 1st-generation immigrant parents and 2.5-generation caregivers with Kibei parents experienced more caregiving difficulties, due to their parents’ limited English proficiency and inability to drive.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Some caregiving experiences of later generations, such as helping with English translation, were similar to what scholars (Kong, 2007; Mokuau & Tomioka, 2010; Sun et al, 2012) previously found among 1st-generation caregivers. Second-generation caregivers with 1st-generation immigrant parents and 2.5-generation caregivers with Kibei parents experienced more caregiving difficulties, due to their parents’ limited English proficiency and inability to drive.…”
Section: Discussionsupporting
confidence: 81%
“…Early studies focused on Black, Hispanic, and non-Hispanic White caregivers (Connell & Gibson, 1997; Dilworth-Anderson, Williams, & Gibson, 2002; Janevic & Connell, 2001). More recent studies address variations between and within Asian and Hispanic caregivers, including sub-ethnic groups (Aranda, Villa, Trejo, Ramírez, & Ranney, 2003; Kong, 2007; Mokuau & Tomioka, 2010; Sun, Ong, & Burnette, 2012). Caregiving challenges resulting from Asian and Hispanic immigration patterns and cultural differences between home and host countries are discussed (Crist & Speaks, 2011; Kong, Deatrick, & Evans, 2010; Zhan, 2004).…”
mentioning
confidence: 99%
“…In China, the traditional culture and Confucianism place a strong emphasis on the importance of family care [3032]. It is a common practice in Chinese hospitals to require the family of a patient to arrange at least one person (either a family member or a paid care worker) to look after the patient.…”
Section: Introductionmentioning
confidence: 99%
“…For example, differences were found in level of stress and coping mechanisms among Korean, Korean-American and Caucasian-American caregivers [45]. Caucasians reported affection while Koreans and Korean Americans reported filial obligation as their motivation for caregiving.…”
Section: Discussionmentioning
confidence: 99%